Cell autoaggregation, biofilm formation, and plant attachment in a sinorhizobium meliloti lpsB mutant - Sorroche, Fernando Guido (2018)
Bacterial surface molecules are crucial for the establishment of a successful rhizobia-legume symbiosis, and, in most bacteria, are also critical for adherence properties, surface colonization, and as a barrier for defense. Rhizobial mutants defective in the production of exopolysaccharides (EPSs), lipopolysaccharides (LPSs), or capsular polysaccharides are usually affected in symbiosis with their plant hosts. In the present study, we evaluated the role of the combined effects of LPS and EPS II in cell-to-cell and cell-to-surface interactions in Sinorhizobium meliloti by studying planktonic cell autoaggregation, biofilm formation, and symbiosis with the host plant Medicago sativa. The lpsB mutant, which has a defective core portion of LPS, exhibited a reduction in biofilm formation on abiotic surfaces as well as altered biofilm architecture compared with the wild-type Rm8530 strain. Atomic force microscopy and confocal laser microscopy revealed an increase in polar cell-to-cell interactions in the lpsB mutant, which might account for the biofilm deficiency. However, a certain level of biofilm development was observed in the lpsB strain compared with the EPS II-defective mutant strains. Autoaggregation experiments carried out with LPS and EPS mutant strains showed that both polysaccharides have an impact on the cell-to-cell adhesive interactions of planktonic bacteria. Although the lpsB mutation and the loss of EPS II production strongly stimulated early attachment to alfalfa roots, the number of nodules induced in M. sativa was not increased. Taken together, this work demonstrates that S. meliloti interactions with biotic and abiotic surfaces depend on the interplay between LPS and EPS II.